Synapsin 2 regulates NCX1 trafficking and is down-regulated in the failing myocardium, which increases the risk of ventricular arrhythmia and heart failure mortality. (3rd October 2022) - Ottesen, A H; Raiborg, C; Melleby, A O; Hansen, M S H; Hafver, T L; Sandbu, R A; Aronsen, J M; Etholm, L; Stokke, M K; Sjaastad, I; Louch, W E; Carlson, C R; et al.
Abstract: Background: Synapsin 2 (Syn2) modulates vesicle transport in the post-synaptic terminal in the brain, and has been linked to sudden unexplained death in epilepsy, but has never previously been studied in the myocardium. Purpose: Given the association of vesicle transport in the brain and the heart, and the similarity of sudden death in epilepsy and cardiac arrhythmias, we have studied the role of Syn2 in the heart. Methods: We explored left ventricular (LV) Syn2 levels in various experimental heart failure (HF) models and assessed mortality in Syn2 knock out (KO) mice vs. wild type (WT) littermates after pressure-overload induced by aortic banding. We used confocal imaging and virus transduction to characterize Syn2 localization and co-localization with NCX and Rab proteins. We verified Syn2-NCX interaction by immunoprecipitation, mass spectrometry, and surface resonance experiments. We investigated calcium handling in isolated cardiomyocytes. Susceptibility for ventricular arrhythmias was also tested in Langendorff-perfused hearts. Results: We found Syn2, but not synapsin 1, to be expressed in the myocardium. LV Syn2 levels were markedly downregulated in the failing myocardium after experimental myocardial infarction or aortic banding. Syn2 KO mice had increased mortality compared to WT littermates following aortic banding, but demonstrated no clear clinical or echocardiographic phenotype, except reduced fractional shortening. Given no clear etiology for increased mortality, we next explored the association between Syn2 and ion-channel vesicle transport, calcium handling and ventricular arrhythmias. By confocal imaging and viral transduction, we found Syn2 to localize in vesicles in HL-1 cells, where Syn2 co-localized with Rab2, Rab3, Rab7 and NCX1. Syn2 was also found to interact with NCX1 as tested by immunoprecipitation, mass spectrometry, and surface resonance experiments. NCX1 levels were downregulated in the membrane fraction in the left ventricle of Syn2 KO mice compared to WT littermates following aortic banding. We observed increased frequency of calcium sparks and waves in isolated Syn2 KO cardiomyocytes compared to controls. We found enhanced susceptibility of Syn2 KO mice for ventricular arrhythmias compared to WT littermates mice during ISO stress testing in explanted hearts. Hearts from Syn2 KO mice also demonstrated more severe ventricular arrhythmias compared to hearts from WT littermates controls. Conclusions: We report for the first time that Syn2 is expressed in the myocardium and that Syn2 seems to regulate NCX1 transport and localization. We also found markedly reduced LV Syn2 levels in HF individuals and mice that lacked Syn2 more frequent displayed severe ventricular arrhythmias and had increased mortality. Hence, our data suggest that reduced Syn2 in the failing myocardium may lead to increased mortality, possibly linked to altered NCX trafficking and subsequent ventricular arrhythmias. Funding Acknowledgement: Type of funding sources: None.